Folic Acid Supplementation Suppresses Sleep Deprivation-Induced Telomere Dysfunction and Senescence-Associated Secretory Phenotype (SASP). (17th December 2019) - Zhang, Xiaoning; Wang, Yuwen; Zhao, Rui; Hu, Xianyun; Zhang, Baoren; Lv, Xin; Guo, Zhenglong; Zhang, Zhiqiang; Yuan, Jinghua; Chu, Xu; Wang, Fei; Li, Guang; et al.
Abstract : Sleep deprivation is reported to cause oxidative stress and is hypothesized to induce subsequent aging-related diseases including chronic inflammation, Alzheimer's disease, and cardiovascular disease. However, how sleep deprivation contributes to the pathogenesis of sleep deficiency disorder remains incompletely defined. Accordingly, more effective treatment methods for sleep deficiency disorder are needed. Thus, to better understand the detailed mechanism of sleep deficiency disorder, a sleep deprivation mouse model was established by the multiple platform method in our study. The accumulation of free radicals and senescence-associated secretory phenotype (SASP) was observed in the sleep-deprived mice. Moreover, our mouse and human population-based study both demonstrated that telomere shortening and the formation of telomere-specific DNA damage are dramatically increased in individuals suffering from sleeplessness. To our surprise, the secretion of senescence-associated cytokines and telomere damage are greatly improved by folic acid supplementation in mice. Individuals with high serum baseline folic acid levels have increased resistance to telomere shortening, which is induced by insomnia. Thus, we conclude that folic acid supplementation could be used to effectively counteract sleep deprivation-induced telomere dysfunction and the associated aging phenotype, which may potentially improve the prognosis of sleeplessness disorder patients.